Spontaneous bile duct perforation in late infancy - Naghi Dara; Hamed Ebrahimibagha; Amirali Soheili; Zhale Nahavandi; Leily Mohajerzadeh; Amirhossein Hosseini; Mohsen Rouzrokh (Journal of Pediatric Surgery Case Reports, 2023)
Spontaneous bile duct perforation (SBDP) is an infrequent condition with no choledochal cyst, bile duct stenosis, or stone. Perforation of the bile duct usually occurs when, for some unexplained cause, the common bile duct becomes obstructed, usually at its distal end at the junction of the cystic duct and common hepatic duct. In most cases, it occurs in early infancy, especially during the first 3 months of age, the occurrence in older ages is very rare. Affected patients have jaundice, failure to thrive, and abdominal protrusion due to ascites, and marked acholic creamy stool which classically leads to the development of bile-stained inguinal or umbilical hernias.Here we report a case of SBDP in late infancy. This case can be an interesting experience.